Effect of Smoking on Tuberculosis Treatment Failure: Meta-Analysis - Tsamarah Nisa; Victoria Sari (Journal of Epidemiology and Public Health, 2022)
Background: Tuberculosis (TB) is an infectious disease that is the leading cause of health problems and death worldwide. Smoking is one of the factors that affect the outcome of TB treatment. This study aims to examine the effect of smoking on TB treatment failure.Subjects and Method: Meta-analysis was carried out according to the PRISMA diagram using the PubMed, Science Direct, and Google Scholar databases. The keywords used ((tuberculosis OR TB) AND (smoking OR tobacco)) AND (impact OR treatment OR outcome OR effect). There were 9 studies with a cohort study design published in 2011-2021 that met the inclusion criteria. The analysis was performed with Revman 5.3.Results: There were 9 articles consisting of 6 studies from Asia (Malaysia, Iran and Armenia), 1 study from North America (Mexico) and 1 study from South America (Brazil) which were included in this meta-analysis. Nine articles showed a significant effect of smoking on TB treatment failure (SMD= 1.88; 95% CI= 1.43 to 2.49; p< 0.001).Conclusion: Smoking can increase tuberculosis treatment failure. Keywords: tuberculosis, smoking, treatment, meta-analysis Correspondence:Victoria Sari. Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir Sutami 36A, Surakarta 57126, Central Java. Email: victoriahusadani@gmail.com. Mobile: 081393539020.